Landscape genetic structure and evolutionary genetics of insecticide resistance gene mutations in Anopheles sinensis. Issue 1 (December 2016) - Chang, Xuelian; Zhong, Daibin; Lo, Eugenia; Fang, Qiang; Bonizzoni, Mariangela; Wang, Xiaoming; Lee, Ming-Chieh; Zhou, Guofa; Zhu, Guoding; Qin, Qian; Chen, Xiaoguang; Cui, Liwang; et al.
Abstract Background Anopheles sinensis is one of the most abundant vectors of malaria and other diseases in Asia. Vector control through the use of insecticides is the front line control method of vector-borne diseases. Pyrethroids are the most commonly used insecticides due to their low toxicity to vertebrates and low repellency. However, the extensive use of insecticides has imposed strong selection pressure on mosquito populations for resistance. High levels of resistance to pyrethroid insecticides and various mutations and haplotypes in thepara sodium channel gene that confers knockdown resistance (kdr ) have been detected inAn. sinensis . Despite the importance ofkdr mutations in pyrethroid resistance, the evolutionary origin of thekdr mutations is unknown. This study aims to examine the evolutionary genetics ofkdr mutations in relation to spatial population genetic structure ofAn. sinensis . Methods Adults or larvae ofAnopheles sinensis were collected from various geographic locations in China. DNA was extracted from individual mosquitoes. PCR amplification and DNA sequencing of thepara-type sodium channel gene were conducted to analysekdr allele frequency distribution, kdr codon upstream and downstream intron polymorphism, population genetic diversity andkdr codon evolution. The mitochondrial cytochromec oxidase COI and COII genes were amplified and sequenced to examine population variations, genetic differentiation, spatial population structure, population expansion and gene flow patterns. Results Three non-synonymous mutations (L1014F, L1014C, and L1014S) were detected at thekdr codon L1014 ofpara-type sodium channel gene. A patchy distribution ofkdr mutation allele frequencies from southern to central China was found. Near fixation ofkdr mutation was detected in populations from central China, but nokdr mutations were found in populations from southwestern China. More than eight independent mutation events were detected in the threekdr alleles, and at least one of them evolved multiple times subsequent to their first divergence. Based on sequence analysis of the mitochondrial COI and COII genes, significant and large genetic differentiation was detected between populations from southwestern China and central China. The patchy distribution ofkdr mutation frequencies is likely a consequence of geographic isolation in the mosquito populations and the long-term insecticide selection. Conclusion Our results indicate multiple origins of thekdr insecticide-resistant alleles inAn. sinensis from southern and central China. Local selection related to intense and prolonged use of insecticide for agricultural purposes, as well as frequent migrations among populations are likely the explanations for the patchy distribution ofkdr mutations in China. On the contrary, the lack ofkdr mutations in Yunnan and Sichuan is likely a consequence of genetic isolation and absence of strong selection pressure. The present study compares the genetic patterns revealed by a functional gene with a neutral marker and demonstrates the combined impact of demographic and selection factors on population structure.